(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
One Farmers use synthetic insecticides to control pests. There are natural enemies that can be used to control P. xylostella pests which until now have not been widely known by farmers. The purpose of this Community Partnership Program Cluster 2 (PKM_K2) activity is to introduce natural enemies to farmer groups that can be used to control P. xylostella pests so that an environmentally friendly and sustainable agricultural system can take place properly. PKM_K2 activities were carried out in Walian II Village, South Tomohon Subdistrict, Tomohon City and the partner was the Skolot Farmer Group. The method of implementation is in the form of direct counseling and discussion with the farmer group. The results of the collaboration between the Skolot Farmers Group and the PKM_K2 Activity Proposal Team of the Faculty of Agriculture Unsrat have succeeded in transferring knowledge, especially about information on the existence of natural enemies of the parasitoid D. semiclausum and how to reproduce these natural enemies. A number of farmers from the Skolot Farmer Group want that activities like this are carried out once a month so that they feel they can compete with cabbage farmers in other regions.